Machine learning in image steganalysis - Schaathun, Hans Georg (Chichester, West Sussex, United Kingdom : IEEE/Wiley, 2012)
'The only book to look at steganalysis from the perspective of machine learning theory, and to apply the common technique of machine learning to the particular field of steganalysis; ideal for people working in both disciplines'--
Front Matter -- Overview. Introduction -- Steganography and Steganalysis -- Getting Started with a Classifier -- Features. Histogram Analysis -- Bit-Plane Analysis -- More Spatial Domain Features -- The Wavelets Domain -- Steganalysis in the JPEG Domain -- Calibration Techniques -- Classifiers. Simulation and Evaluation -- Support Vector Machines -- Other Classification Algorithms -- Feature Selection and Evaluation -- The Steganalysis Problem -- Future of the Field -- Bibliography -- Index.
Includes bibliographical references and index.
Print version record and CIP data provided by publisher.
Keywords: Machine learning; Wavelets (Mathematics); Data encryption (Computer science); Machine learning; Wavelets (Mathematics); Data encryption (Computer science); SCIENCE -- Waves & Wave Mechanics; Data encryption (Computer science); Machine learning; Wavelets (Mathematics); Machine learning; Wavelets (Mathematics); Data encryption (Computer science); Electronic books